The Effect of Advanced Practice Nurse-Led Intervention Program on Outcomes in Diabetes Patients with Complex Problems - Jerawatana, Ratanaporn; Reutrakul, Sirimon; Siripitayakunkit, Apinya (Nursing Research and Innovation Journal, 2018)
The purpose of this quasi experimental study was to examine the effect of APN led intervention program on knowledge, self-care activities, quality of life, and glycemic control in patient with diabetes. Orem’s Self- Care theory, the motivational interviewing, and evidence-based approach provided the theoretical framework of this study. A total of 30 diabetes patients admitted in Ramathibodi hospital was recruited. The program consisted of 3 phases within 10 weeks. In phase 1, promoting self-awareness of patient health status and raise motivation by APN via individual education and skill training then planning individual goal setting for behaviour change, in a one week with 3 visits. In addition, phase 2: developing self-care abilities in 2nd week and facilitate appropriately resource mobilization for self-monitoring. Finally, phase 3: Empowerment to continue self-care by APN in every 2 week home telephone counselling, and in case of emergency, APN opens hotline telephone call for 24 hours until 12th week. Self-care activities, quality of life, and glycemic control were measured at baseline and 12 weeks after the baseline. Paired t test and Friedman test were used to analyse the data. The study finding showed that the mean scores of knowledge, self-care activity and quality of life were significantly higher than before entering the program. Moreover, the mean percentage of glycosylated hemoglobin (HbA1c) decreased significantly from 11.43% to 7.29%. The study finding revealed that the effectiveness of APN led diabetes program for improving both physiological and psychological outcomes and maintaining continuity of care. Therefore, implementing the APN led program in diabetes patient with complex problems should be translated into practice in a complex health care system.